2018
DOI: 10.1371/journal.pone.0208752
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic investigations in cerebrospinal fluid of Parkinson's disease

Abstract: The underlying mechanisms of Parkinson´s disease are not completely revealed. Especially, early diagnostic biomarkers are lacking. To characterize early pathophysiological events, research is focusing on metabolomics. In this case-control study we investigated the metabolic profile of 31 Parkinson´s disease-patients in comparison to 95 neurologically healthy controls. The investigation of metabolites in CSF was performed by a 12 Tesla SolariX Fourier transform-ion cyclotron resonance-mass spectrometer (FT-ICR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 64 publications
3
55
0
1
Order By: Relevance
“…Alterations in levels of TCA cycle metabolites have been reported previously in relation to PD. For instance, an increased malate concentration was found in plasma (49), and an increased citrate concentration in the CSF (50) of PD patients. In contrast, decreased levels of several TCA metabolites (citrate, malate, succinate, and isocitrate) have also been detected in brains from PD patients (51).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in levels of TCA cycle metabolites have been reported previously in relation to PD. For instance, an increased malate concentration was found in plasma (49), and an increased citrate concentration in the CSF (50) of PD patients. In contrast, decreased levels of several TCA metabolites (citrate, malate, succinate, and isocitrate) have also been detected in brains from PD patients (51).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many studies focused on metabolic biomarker screening (comparing healthy subjects with either familial PD or idiopathic PD), for an early detection of potential development of PD. The metabolic profiles of PD patients (in cerebrospinal fluid (CSF), blood or urine) usually reflect oxidative stress [24,[27][28][29][30][31] or mitochondrial dysfunction [24,[31][32][33][34][35]. However, many studies also observed differences in metabo-lites from bacterial origin, which are summarized in Table 2.…”
Section: Altered Bacterial-derived Metabolites In Patients With Parkimentioning
confidence: 99%
“…Taken together, data available suggest that altered levels of IAA, which are caused by changes in microbial composition, might play a role in attenuating inflammation in PD patients. p-Cresol sulfate (sulfonated by the liver), which is exclusively produced by gut bacteria [53], mainly by species belonging to Clostridiaceae (Clostridium clusters I, IV, IX, XI, XIII, XIVa, XVI) and Bacteroidaceae families [54] (Table 1), is also observed to be ∼10 fold increased in in the CSF of PD patients [31] but not in blood samples [24,28]. However, differential metabolite levels in blood do not necessarily reflect CSF levels [55].…”
Section: Altered Bacterial-derived Metabolites In Patients With Parkimentioning
confidence: 99%
“…Moreover, gut microbiota modifications could reflect changes in bacterial metabolites. To date, several studies have investigated the metabolomics profile of PD patients in different biological samples, such as cerebrospinal fluid, blood, and urine (21)(22)(23)(24)(25)(26). However, only a few studies have explored the fecal metabolome that mirrors the status of colonic bacteria and also links the symbiotic microbiota and health.…”
mentioning
confidence: 99%